Pentingnya Percaya Kepada Kristus dan Taat Terhadap Firman Allah : Studi Eksposisi Ibrani 2:1-4 - Operman Zandroto; Ferdinan Halawa; Malik Bambangan (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This research examines the significance of faith in Christ and obedience to God's word based on Hebrews 2:1-4. This passage delivers a strong warning not to overlook the extraordinary salvation revealed through Jesus Christ. The study seeks to explore the theological meaning and practical application of this message in the lives of believers, employing a hermeneutical method to thoroughly analyze the text, considering the historical, cultural, and theological contexts of the Letter to the Hebrews. The findings indicate that Hebrews 2:1-4 conveys a crucial message to humanity to attentively heed the Gospel and avoid influences that might lead them away from the truth. The passage highlights three key points: first, the supremacy of Christ as the ultimate revelation of God; second, the severe consequences of neglecting the salvation offered through Him, which is reinforced by signs, wonders, and the gift of the Holy Spirit, validating the authority of the Gospel. Moreover, the study stresses the need for an active response from believers to God's word through strong faith and consistent obedience. The conclusion reveals that faith in Christ and obedience to God's word are not only the foundational aspects of spiritual life but also an ethical response to the gift of salvation. In practical terms, Christians are encouraged to renew their commitment to living in accordance with God's word as a way to honor the redemptive work of Christ. This research contributes to the understanding of Christian theology and its relevance to daily life.